ANALISIS HASIL POTONG PLAT BAJA PADA GUNTING TUAS DENGAN VARIASI CLEARENCE DAN SUDUT POTONG PISAU - R. N. Akhsanu Takwim; Subagiyo Subagiyo (INFO-TEKNIK, 2017)
Often the cut side of the plate pieces on the lever scissors is not good (distortion occurs). This is due to the incompatibility of cutting variables, such as clearance and cutting angle of both scissors knife. The extent to which the effect of the clearance and the cutting edge of the scissor knife on the cutting of the steel plate is to be studied to obtain the appropriate cutting parameter as reference in the slashing work of the plate with the lever scissors.This research is aimed to know the proper clearance and cutting angle for various variations of steel plate thickness. The thickness of the steel plate as a specimen of the test specimens was of a size 1.61 mm, 2.63 mm, 3.85 mm, 4.95 mm and 5.39 mm, respectively. While the variation of cutting angle of scissor knife include: 75o, 77,5o, 80o, 82,5o and 85o.The test results showed that cutting of 1.61mm thick steel plate with 0.5 mm clearance and 77,5o cutting angle resulted in good cuts with 45% incision depth. On steel plates with thickness of 2.63mm and 3.85mm, the best cut results at 1mm clearance and cutting angle of scissors knife 77,5o, where the depth of incision successively reached 35% and 25%. For thick plates 4.95 mm and 5.39 mm, the best results of the incision depth were respectively 20% and 18% on clearance 2 mm and cutting angle 82,5o.